2022
DOI: 10.1038/s41379-021-00953-0
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of chemotherapy-treated stage III colorectal cancer patients using multiplexed imaging and single-cell analysis of T-cell populations

Abstract: Colorectal cancer (CRC) has one of the highest cancer incidences and mortality rates. In stage III, postoperative chemotherapy benefits <20% of patients, while more than 50% will develop distant metastases. Biomarkers for identification of patients at increased risk of disease recurrence following adjuvant chemotherapy are currently lacking. In this study, we assessed immune signatures in the tumor and tumor microenvironment (TME) using an in situ multiplexed immunofluorescence imaging and single-cell analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Our comparatively small sample size is explained by the specificity of the population targeted by our study, and is similar to the sample size of other surveys recently published on this particular population 35,36 . However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our comparatively small sample size is explained by the specificity of the population targeted by our study, and is similar to the sample size of other surveys recently published on this particular population 35,36 . However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Discussionmentioning
confidence: 52%
“…Heeg et al 34 population. 35,36 However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Weaknesses and Strengths Of This Studymentioning
confidence: 99%
“…Recent advances of single cell technologies have led to a surge of studies that generate tissue specific genomic profiles at atlas scale. The HuBMAP consortium is one such effort generating several tissue-specific single cell genomic data sets ( 91–93 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that previous studies suggested a positive association between regulatory T‐cells and worse outcome [ 39 ] should be interpreted taking into account differences in the clinical characteristics of the cohorts studied and the methods used to quantify regulatory T‐cells. Further, one study analyzing chemotherapy‐treated stage III colorectal carcinomas found improved outcomes for regulatory T‐cell tumors [ 40 ].…”
Section: Discussionmentioning
confidence: 99%